Effective Medicinal Plants in the Treatment of the Cyclic Mastalgia (Breast Pain): A Review - Azin Niazi; Vafa Baradaran Rahimi; Hooman Hatami; Reza Shirazinia; Reza Esmailzadeh-dizaji; Nafiseh Askari; Vahid Reza Askari (Korean Pharmacopuncture Institute, 2019)
Introduction: Mastalgia is the most common benign breast disorder during the fertility period of women. So far a wide range of natural or complementary medicines is used to cure mastalgia. Sanitary organizations need complete and suitable details to help women, for making the proper decision for alternative treatment based on the evidence. The aim of the present study is to introduce medicinal plant-based treatments about mastalgia and summarizes clinical trials about this disorder. Method: The articles were provided using mixture of keywords including cyclic pain, breast, treatment, therapeutics, therapy, clinical trial, herbal, drug, mastalgia and all the probable terms, in national and international databases SID, Iran Medex, Magiran, PubMed, Scopus, Medline, Science direct and Cochrane library, in both Persian and English languages. All cross-sectional and review articles about herbal treatment of mastalgia until 2018 November were studied. Results: Nineteen articles from all of the available articles (45 cases) and a sample size about of (1987 cases) were included in our study. The articles were clinical trials. The results revealed that mastalgia could be healed by Nigella sativa, Vitex agnus-castus, curcumin, Hypericum perforatum, Citrus sinensis, wheat germ, and Ginkgo biloba. Conclusion: Most of the evaluated medicinal plants possessing antioxidant compounds with anti-inflammatory and analgesic properties, exhibited healing effects in the treatment of mastalgia. Thus, medicinal plants can be considered in the treatment of mastalgia; however, further investigations are needed to obtain more details about their probable side effects.